Analysis of a Fast-Moving Landslide during an Earthquake in Japan - K. Ishihara (International Association of Lowland Technology, 2017)
In an effort to determine the residual strength from the laboratory tests, a new type of tests termed “constant-volume triaxial test” was performed on non-saturated specimens of silty sand prepared at varying water contents. The results of the tests disclosed that the water content or saturation ratio is a key parameter governing the residual strength of the non-saturated soil tested in the above manner. Back-analysis was also made to determine the residual strength that might have been mobilized in the landslide triggered at Tsukidate at the time of the May 26, 2003 earthquake. The comparison of these two data showed a reasonable degree of coincidence, indicating that the proposed method of the laboratory triaxial tests would be a promising means for estimating the residual strength of given soils.